(3JWHjbGJ GdGfJQfJ aj GdJShjbs - (3HTjQ YHGS(B, (3GdYdGbs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2003)
(3ebOeI aj GdJShjb aj YUQ GdCfJQfJ(B- (3OhQ JcfhdhLjG GdeYdheGJ aj JMSjf EfJGLjI GdJShjb(B- (3GdEJUGdGJ GdJShjbjI aj YUQ GdCfJQfJ hGdEbJUGO GdQbej(B- (3GdEYdGf YHQ GdCfJQfJ(B- (3efXhQ JShjbj LOjO ddJLGQI GdCdcJQhfjI(B- (3GdJShjb GdOhdj hGdCfJQfJ(B- (3GdJShjb YHQ GdYdGbGJ GdeSJfOI ddJcfhdhLjGs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdEdcJQhfjs